External Effects of the War in Ukraine: The Impact on the Price of Oil in the Short-term - Garzon Gordon, Antonio Jose; Hierro Recio, Luis Angel (International Journal of Energy Economics and Policy, 2019)
This paper analyses the short-term impact of the most relevant events of the war in the Ukraine on the price of oil. In order to determine the events to be studied, we propose a methodology based on a study of the news published in two reference newspapers in the markets: the Wall Street Journal and the Financial Times. From this selection, we use an event study model to detect the significance of the events. The main results obtained are: events that affected daily oil prices were scarce and occurred during very specific phases of the conflict; WTI price was more affected than Brent, even though the war took place in Europe; there is no noticeable lagged effect in the events, suggesting that the market assimilated the impact of relevant events very quickly. Keywords: oil price, war, Ukraine, event study JEL Classifications: F51, G14, Q40 DOI: https://doi.org/10.32479/ijeep.7380